Impact of a Cardiology-Based Shock Team on Institutional Venoarterial Extracorporeal Membrane Oxygenation Use for Cardiogenic Shock - Moein Bayat Mokhtari, MD; Abduljabar Adi, MD; Chad A. Kliger, MD; Arber Kodra, MD; Sirish Vullaganti, MD; Miguel Alvarez Villela, MD (Texas Heart Institute Journal)
None.